The strategy of appropriating someone else’s identity: Pseudo-Pushkin - A. V. Dubrovskii (Шаги)
Based on the pseudo-Pushkin texts, the paper examines the strategy of appropriating someone else’s identity as a manifestation of mass culture. The “Pseudo-Pushkin” phenomenon appeared during the poet’s lifetime, when his epigrams and impromptus began to spread in society, and the Pushkin myth began to arise. “Pseudo-Pushkin” became a part of this myth. It manifested itself in various forms: in the contemporary press, in more or less authoritative copies, in foreign or illegal publications, in collected works. The texts attributed to Pushkin may be anonymous, pseudonymous, cryptonymous, collective, or signed with his full name. They are extremely diverse in terms of genre: poems, epigrams, impromptus, articles, “Secret Notes”, drawings, etc. Especially many of the Pseudo-Pushkin texts appeared in the second half of the nineteenth century after the publication of his collected works by Pavel V. Annenkov. At this time, there was a need in society to collect everything that was written by Pushkin and to complete the publication of Annenkov with unpublished texts. A great many pseudo-Pushkin poems were published by P.A. Efremov, another editor of Pushkin. This trend continued in the 20th century, especially during the celebration of Pushkin`s anniversaries. The question is raised how and why people of the most diverse character, upbringing, education, professional training, not to mention the difference of epochs, are seized by a desire to discover a hitherto unknown Pushkin. As an example of journalistic and editorial mistakes we consider the history of a handwritten notebook, known as A.A. Kraevsky’s — V.G. Belinsky’s notebook.